Robotic sacrocolpopexy: a game worth playing? A critical literature analysis - Mansour Jamaleddine, Hussein; Khalil, Nour; Aoun, Rana; Atallah, David (Frontiers in Surgery, 2025)
Robotic sacrocolpopexy is an advanced minimally invasive technique for the surgical management of urogenital prolapse. It offers superior precision, reduced blood loss, and lower conversion rates compared to traditional approaches. However, longer operative times, higher costs, and the need for specialized training remain the most significant challenges of robotic surgery. The advantages of robotic sacrocolpopexy are reduced intraoperative complications, lower blood loss, and decreased conversion rates compared to traditional approaches. However, it was described to involve longer operative times, increased costs, and the need for a specialized training. Additionally, the technique shows significant potential for reducing complications in obese patients and improving cosmetic outcomes. Comparative studies highlight that robotic and laparoscopic sacrocolpopexy yield similar long-term outcomes, with differences primarily in operative time and cost-efficiency robotics. The lack of standardized protocols remains a limitation, and long-term data on durability and cost-benefit analyses are needed. Future research should prioritize optimizing outcomes, reducing costs, and improving accessibility to robotic urogynecologic surgery.